2020
DOI: 10.1002/hep.30954
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐Inducible Factor‐2α Reprograms Liver Macrophages to Protect Against Acute Liver Injury Through the Production of Interleukin‐6

Abstract: BaCKgRoUND aND aIMS: Acetaminophen (APAP) overdose represents the most frequent cause of acute liver failure, resulting in death or liver transplantation in more than one third of patients in the United States. The effectiveness of the only antidote, N-acetylcysteine, declines rapidly after APAP ingestion, long before patients are admitted to the clinic with symptoms of severe liver injury. The direct hepatotoxicity of APAP triggers a cascade of innate immune responses that may exacerbate or limit the progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 50 publications
(65 reference statements)
4
50
0
Order By: Relevance
“…149 A recent study demonstrated that HIF-2α in hepatic macrophages induces IL-6 production and promotes hepatocyte survival through STAT3 activation during AILI. 153 In ALD, IL-6 produced by KCs triggers hepatocyte senescence, rendering hepatocytes resistant to alcohol-induced apoptosis as a protective mechanism. 154 To promote tissue repair, macrophages secrete mediators involved in tissue growth (e.g., IGF) and remodeling (e.g., MMPs) in liver diseases, including AILI, ALD, and fibrosis.…”
Section: Roles Of Macrophages In Resolving Inflammation During Liver mentioning
confidence: 99%
“…149 A recent study demonstrated that HIF-2α in hepatic macrophages induces IL-6 production and promotes hepatocyte survival through STAT3 activation during AILI. 153 In ALD, IL-6 produced by KCs triggers hepatocyte senescence, rendering hepatocytes resistant to alcohol-induced apoptosis as a protective mechanism. 154 To promote tissue repair, macrophages secrete mediators involved in tissue growth (e.g., IGF) and remodeling (e.g., MMPs) in liver diseases, including AILI, ALD, and fibrosis.…”
Section: Roles Of Macrophages In Resolving Inflammation During Liver mentioning
confidence: 99%
“…T-cells-specific deletion of HIF1-α increases neutrophil infiltration and the recruitment of aberrant γδ T-cells into the liver, finally favoring acute hepatic inflammation [ 115 ]. Genetic deletion of the HIF2-α gene in myeloid cells reduces the progression of acute liver disease by inducing liver macrophages to overexpress IL-6 and protects against acute injury [ 116 ].…”
Section: Dual Role Of Hypoxia In Acute and Chronic Disease Conditimentioning
confidence: 99%
“…IL-6 and PDGF-B were significantly higher in Entdp2 null mice compared to WT. Whereas TNF-α is most commonly viewed as a pro-inflammatory agent in acute liver failure [ 27 , 28 ], IL-6 can directly protect hepatocytes from oxidative stress after APAP toxicity, and both have long been known to stimulate liver regeneration [ 29 , 30 ]. PDGF-B and TGF-β are secreted by damaged hepatocytes after toxic insults and can stimulate regeneration, but can also trigger induction of fibrosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%